Surgical treatment of aneurysms of the ascending aorta associated with severe aortic regurgitation. - Antunes, M J (1984)
From January 1979 to June 1982 31 patients have had simultaneous ascending aortic aneurysm repair and aortic valve replacement. Fifteen patients (group 1) received a composite graft; seven patients (group 2) had separate aortic valve and supracoronary ascending aorta prostheses; and nine patients (group 3) had aortic valve replacement and "tailoring" of the ascending aorta. The mean age was 50 (SD 14) years. Nine patients had acute dissection, five with the coronary ostia affected. Emergency surgery was performed in 10 cases. There were six early deaths (19.4%), none of them due to technical complications during surgery. The mortality rate was 56% for patients with acute dissection operated on as an emergency and 4.5% for patients having elective operations. Appreciable haemorrhage occurred in four patients (12.9%). No neurological complications occurred. There was one late death. The survivors were followed up for one to four years. There was one case of recurrence of aneurysm. No ischaemic complications resulted from coronary reimplantation. There were no significant differences in the results of the three groups. Simultaneous ascending aortic aneurysm repair and aortic valve replacement can be accomplished with an acceptable mortality rate and little morbidity.